Knowledge development visualization and mapping path of the psychological capital research - Meng, Sun; Fu, Xinwei; Luo, Danxue (Frontiers in Psychology, 2022)
With the respect to the key factors, namely the psychological state of individuals and organizations, psychological capital (PsyCap) is widely used in various fields, such as management decisions and organizational behavior. To fully show the related studies and their knowledge development and mapping path, in this paper, we examine 2786 papers about the PsyCap related research from 1970 to 2021. Based on the bibliometric analysis and main path demonstration (the tools are Cite-Space and Pajke, respectively), we derive some conclusions as follows: (1) the publication number about the PsyCap study is growing rapidly and it is a highly cross-cutting research topic. (2) The main authors come from Australia, the United States, and China, and also are the core researchers of the PsyCap study. (3) It is found that two concepts of refinement and measurement in the PsyCap study are constant and hot topics. (4) Many related references focus on the issues of stress, performance, and well-being of students, healthcare workers, and corporate employees. (5) These studies also show that team organization, creativity, innovation, and COVID-19 are hot topics in this field. After that, we provide the main path analysis of the PsyCap research from four perspectives, including global key route, global standard route, local forward route, and local backward route, so that to better understand the further trends and directions in the PsyCap research field.